2016
DOI: 10.1200/jco.2016.34.15_suppl.e13044
|View full text |Cite
|
Sign up to set email alerts
|

Statins and risk of breast cancer recurrence.

Abstract: Background:The primary end point of our study was to test whether the concurrent use of a statin is related to a lower risk of recurrence and increased relapse-free survival in patients with early breast cancer. Materials and methods:We reviewed 610 female patients with stage I, II, or III breast cancer who had been surgically treated and who had subsequently received at least adjuvant chemotherapy in order to prevent recurrence. Results: Among the 610 patients with breast cancer, 83 (13.6%) were receiving a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 49 publications
(72 reference statements)
1
13
0
Order By: Relevance
“…We found that tumors positive for HER2 had more decline in Ki67 compared with those negative for it but with statistically insignificant difference, these finding also observed in Yulian et al study who investigated the role of statin (simvastatin) in inhibiting proliferation of breast cancer cells, but they found significant difference in both HER2 positive and HER2 negative tumors [18], our expectation was that these molecular factors would significantly affect the treatment response in term of comparable decrease in Ki67 index, but the results were contrary to our expectation. In our study, we found that the most factor that has impact on post-treatment ki67 changes is tumor grade, regarding the tumor grade, there were four cases (13.3%) with grad I, sixteen (53.3%) with grade II and ten (33.3%) with grade III, after treatment with atorvastatin there was remarkable Ki67 changes regarding tumor grade, in grade I cases, 50% of them had unchanged Ki67, 25% increased and 25% decreased , in grade II cases, 6.3% of them had unchanged Ki67, 56.3% decreased and 37% increased compared with those with grade III, in whom Ki67 decreased in 90% of them (p=0.05) with statistically significant difference (Table 3), these results were similar in various studies that were conducted to evaluate the role of statins in breast cancer [1,3,18,19]. Finally, the antiproliferative effect of statins, which was established in this study, was supported by previous in-vitro and in-vivo studies not only in breast cancer, but also in other malignancies [20][21][22] and encouraging further researches to incorporate statins in the neo-adjuvant and adjuvant breast cancer treatment.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…We found that tumors positive for HER2 had more decline in Ki67 compared with those negative for it but with statistically insignificant difference, these finding also observed in Yulian et al study who investigated the role of statin (simvastatin) in inhibiting proliferation of breast cancer cells, but they found significant difference in both HER2 positive and HER2 negative tumors [18], our expectation was that these molecular factors would significantly affect the treatment response in term of comparable decrease in Ki67 index, but the results were contrary to our expectation. In our study, we found that the most factor that has impact on post-treatment ki67 changes is tumor grade, regarding the tumor grade, there were four cases (13.3%) with grad I, sixteen (53.3%) with grade II and ten (33.3%) with grade III, after treatment with atorvastatin there was remarkable Ki67 changes regarding tumor grade, in grade I cases, 50% of them had unchanged Ki67, 25% increased and 25% decreased , in grade II cases, 6.3% of them had unchanged Ki67, 56.3% decreased and 37% increased compared with those with grade III, in whom Ki67 decreased in 90% of them (p=0.05) with statistically significant difference (Table 3), these results were similar in various studies that were conducted to evaluate the role of statins in breast cancer [1,3,18,19]. Finally, the antiproliferative effect of statins, which was established in this study, was supported by previous in-vitro and in-vivo studies not only in breast cancer, but also in other malignancies [20][21][22] and encouraging further researches to incorporate statins in the neo-adjuvant and adjuvant breast cancer treatment.…”
Section: Discussionsupporting
confidence: 76%
“…1). In the pre-treatment sample, the mean Ki67 index was 16.10 range [12][13][14][15][16][17][18][19][20], in comparison, in post treatment samples, the mean Ki67 index was 13.90 range [10][11][12][13][14][15][16][17][18][19] with average absolute reduction 2.2 percentage points (P = 0.001). (Table 2) The relation between clinicopathological variables and Ki67 changes were analyzed to predict the factors that may affect the response to treatment ( Table 3).…”
Section: Treatment Outcomementioning
confidence: 99%
“…Besides some minor discrepancies, several cohort studies or clinical trials showed accumulating evidence of the clinical benefits of statins for breast cancer patients, via nonlipid-lowering therapeutic effects, aka pleiotropic effects. [3][4][5] The involvement of glucoseand cholesterol-rich diets in the metabolic reprogramming of cells and the augmentation of the oncogenic process have also been reported. 6 Cholesterol plays vital metabolic and structural roles in the cells.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, the investigation of pleiotropic effects sometimes reveals novel applications of clinically proven medicines. Besides some minor discrepancies, several cohort studies or clinical trials showed accumulating evidence of the clinical benefits of statins for breast cancer patients, via nonlipid‐lowering therapeutic effects, aka pleiotropic effects . The involvement of glucose‐ and cholesterol‐rich diets in the metabolic reprogramming of cells and the augmentation of the oncogenic process have also been reported .…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps of greatest interest was our demonstration that simvastatin combined with an IL-12-secreting DC-based therapy significantly retarded tumor growth kinetics while single treatments did not. We predicted this would be the case, since both Th1 immunity and statin use has been associated with better outcomes for breast cancer [49,50]. Even a single parenterally supplied Th1 cytokine (IFN-γ) showed substantial increased activity in combination with simvastatin in the mouse model ( Figure 8F), consistent with the notion that Th1 cytokines are major effector mechanisms of DC immunotherapy induced responses in this model, and furthermore suggesting a non-cell-based immunotherapy (i.e., a recombinant cytokine) that can be used in combination with simvastatin to achieve an anti-tumor effect.…”
Section: Discussionmentioning
confidence: 99%